Moral values in The Martian (2015) - Susilawati Susilawati; Ai Purnamasari (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2019)
The objectives of this study entitled “An Analysis Of Moral Values As Portrayed By Mark Watney’s Characteristics In “The Martian” Movie Script, are: (1) to describe Mark Watney’s characteristics in “The Martian (2015)” movie script. (2) to analyze the moral values as portrayed by Mark Watney’s characteristics in “The Martian (2015)” movie script. The investigation of moral values in this study used a definition proposed by Thomas Lickona. This study used qualitative content analysis approach. The instrument of this research is human as the researcher and the data sheet. The data used of this study are words and sentences. The validity used is theoretical validity and investigator validity. This study indicated that characteristics of Mark Watney is a sense of humor, a supremely chill guy, and a spirit of survival and soul. Moral values that portrayed by Mark Watney’s characteristics is sense of humor, self-control, self-confidence, humility, intellectual curiosity, hard-working, problem solving, courage, and integrity. Keywords : Movie; Characteristics; Moral Values